American pentimento : the invention of Indians and the pursuit of riches - Seed, Patricia (Public worlds ;, 2001)
An illuminating examination of colonizations ongoing cultural legacy. Patricia Seed examines how European countries, primarily England, Spain, and Portugal, differed in their colonization of the Americas, with the English appropriating land, while the Spanish and Portuguese attempted to eliminate "barbarous" religious behavior and used indigenous labor to take mineral resources. Seed also demonstrates how these antiquated cultural and legal vocabularies are embedded in our languages, popular cultures, and legal systems, and how they are responsible for current representations and treatment of Native Americans.